2015
DOI: 10.1152/ajpheart.00820.2014
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin promotes the proliferation and migration of vascular smooth muscle and increases mouse blood pressure

Abstract: Blood chemerin concentration shows positive correlation not only with body mass index and serum triglyceride level but also with systolic blood pressure. While it seems likely that chemerin influences vascular smooth muscle cell (SMC) proliferation and migration, which are crucial to the development of hypertension, this remains to be clarified. In the present study, we investigated whether chemerin controls SMC proliferation and migration in vitro and also affects blood pressure in vivo. In vitro, chemerin si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 43 publications
2
59
1
Order By: Relevance
“…Erk MAPK and PLC are not involved in chemerin-dependent calcium flux and contraction. With a host of literature describing the possibility of chemerin’s involvement in hypertension [39], further research is needed to connect this knowledge with an actual treatment. This specific pathway helps to characterize a once unknown mechanism by which chemerin may contribute to obesity-related hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erk MAPK and PLC are not involved in chemerin-dependent calcium flux and contraction. With a host of literature describing the possibility of chemerin’s involvement in hypertension [39], further research is needed to connect this knowledge with an actual treatment. This specific pathway helps to characterize a once unknown mechanism by which chemerin may contribute to obesity-related hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of white adipose tissue through exercise or bariatric surgery reverses the levels of circulating chemerin [7]. Additionally, the active form of chemerin (chemerin S 157 ) is positively associated with blood pressure in both humans [8] and mice [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Kaur et al (17) identified ChemR23 in human endothelial cells, and Kostopoulos et al (19) confirmed chemerin and ChemR23 expression in human arteries and PVAT. More recently, infusion of chemerin into the mouse modestly elevated blood pressure (20), and chemerin has been suggested to reduce nitric oxide signaling in the rat aorta (29). Understanding the functions of chemerin is important, because circulating levels of chemerin can be reduced and health can be improved through a number of interventions that include bariatric surgery and exercise (7,22,24,28,30,34,39,44).…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, the effect of chemerin as a growth factor in vascular biology was investigated. It was reported that chemerin significantly induced rat arterial smooth muscle cells proliferation as well as migration and increased systolic blood pressure [26]. It was also reported that elevated circulatory and local (periaortic and epicardial adipose tissue) chemerin levels significantly increased and positively correlated with the severity of coronary artery disease [12, 2729].…”
Section: Discussionmentioning
confidence: 99%